2022
DOI: 10.3389/fchem.2022.894603
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Compatible Suzuki-Miyaura Cross-Coupling Reaction of Aryl Iodides With (Hetero)Aryl Boronic Acids for DNA-Encoded Libraries

Abstract: An efficient method for the C-C bond formation via water soluble Na2PdCl4/sSPhos mediated Suzuki-Miyaura cross-coupling reaction of DNA-conjugated aryl iodide with (het)aryl boronic acids has been developed. This reaction proceeds at 37°C in water and acetonitrile (4:1) system. We also demonstrated that numerous aromatic and heteroaromatic boronic acids of different electronic natures, and harboring various functional groups, were highly compatible providing the desired coupling products in good to excellent y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In 2022, Flajolet and Siripuram 61 reported an effective protocol for Suzuki–Miyaura cross-coupling on a DNA-conjugated aryl iodide with aryl and heteroaryl boronic acids using a water-soluble catalyst. After thorough optimization of the conditions, the Suzuki–Miyaura reaction of DNA conjugated aryl iodide ( 26 ) was carried out using Na 2 PdCl 4 /sSPhos and potassium carbonate with the reaction proceeding at 37 °C in H 2 O : CH 3 CN (4 : 1) solvent system (Scheme 11).…”
Section: Transition-metal Mediated Cross-coupling Reactions For Dna-e...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Flajolet and Siripuram 61 reported an effective protocol for Suzuki–Miyaura cross-coupling on a DNA-conjugated aryl iodide with aryl and heteroaryl boronic acids using a water-soluble catalyst. After thorough optimization of the conditions, the Suzuki–Miyaura reaction of DNA conjugated aryl iodide ( 26 ) was carried out using Na 2 PdCl 4 /sSPhos and potassium carbonate with the reaction proceeding at 37 °C in H 2 O : CH 3 CN (4 : 1) solvent system (Scheme 11).…”
Section: Transition-metal Mediated Cross-coupling Reactions For Dna-e...mentioning
confidence: 99%
“…In 2022, Flajolet and Siripuram 61 reported an effective protocol for Suzuki-Miyaura cross-coupling on a DNAconjugated aryl iodide with aryl and heteroaryl boronic acids using a water-soluble catalyst. After thorough optimization of the conditions, the Suzuki-Miyaura reaction of DNA conjugated aryl iodide (26) was carried out using Na 2 PdCl 4 /sSPhos and The authors demonstrated the scope of the reaction with numerous aryl and hetero aryl boronic acids having different electronics and bearing various functional groups, providing products in good to excellent yields.…”
Section: Introductionmentioning
confidence: 99%
“…2 The chemical diversity of the DEL is crucial to the successful discovery of bioactive compounds. 3 In recent years, efforts have been focused on exploiting various DNA-compatible chemical reactions to expand the library diversity of the DEL, including reactions to connect building blocks with carbon–carbon 4 or carbon–heteroatom linkers 5 and reactions to assemble medicinally privileged scaffolds via cyclization. 6 Besides these methods that directly contribute to library diversity, DNA-compatible functional group transformation has been limited to a few cases and relatively underscored, 7 possibly because functional group transformation did not directly add extra dimensions of building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts have generated a few DNA-compatible Pdcatalyzed C-C cross-coupling reactions. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] A suite of synthetic methodologies realized robust Suzuki-Miyaura coupling between a diverse set of DNA-tethered aryl halides (X = I, Br, or Cl) and boronic acids/esters. [40][41][42][43][44][45][50][51][52][53]55 Besides, efficient Pd-catalyzed DNA-compatible Heck coupling reactions between olens and aryl halides were exploited.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] A suite of synthetic methodologies realized robust Suzuki-Miyaura coupling between a diverse set of DNA-tethered aryl halides (X = I, Br, or Cl) and boronic acids/esters. [40][41][42][43][44][45][50][51][52][53]55 Besides, efficient Pd-catalyzed DNA-compatible Heck coupling reactions between olens and aryl halides were exploited. 46,47 However, most approaches generally employ harsh conditions such as elevated temperatures (>50 °C) and strong bases, which might cause DNA and functional group damage (Fig.…”
Section: Introductionmentioning
confidence: 99%